2003
DOI: 10.1021/ac026379k
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Liquid Arrays for Simultaneous Detection of Simulants of Biological Warfare Agents

Abstract: Liquid array-based multiplexed immunoassays designed for rapid, sensitive, specific, and simultaneous detection of multiple simulants of biological warfare agents have been developed. In both blind and standard laboratory trials, we demonstrate the simultaneous detection of four simulant agents from a single sample. The challenge agents comprise broad classes of pathogens (virus, protein toxins, bacterial spores, vegetative cells). Assay performance of each analyte was optimized, and dose-response curves and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(119 citation statements)
references
References 24 publications
5
113
0
1
Order By: Relevance
“…The LOD of MIA was similar to ELISA for extracts in which bacteria were detected without previous enrichment. Also in previous comparative studies, the sensitivity of MIA was often similar to ELISA (Dasso et al, 2002;McBride et al, 2003). The LODs of MIA for detection of Pca and Dcd in peel extracts were rather high compared to those published for other bacteria (Dunbar et al, 2003) in which the authors reported a sensitivity of ca.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The LOD of MIA was similar to ELISA for extracts in which bacteria were detected without previous enrichment. Also in previous comparative studies, the sensitivity of MIA was often similar to ELISA (Dasso et al, 2002;McBride et al, 2003). The LODs of MIA for detection of Pca and Dcd in peel extracts were rather high compared to those published for other bacteria (Dunbar et al, 2003) in which the authors reported a sensitivity of ca.…”
Section: Discussionmentioning
confidence: 58%
“…An assortment of 100 beads are available, each with a unique composition of red and infrared fluorochromes. The Luminex technology has proven its value already for multiplex detection of target compounds in the field of human diagnostics (Kellar, 2003), food microbiology (Dunbar et al, 2003), environmental microbiology (Spiro and Lowe, 2002) and biological warfare (McBride et al, 2003;Biagini et al, 2004) by using protein and nucleic acid-based techniques. Beads can be covalently coupled with proteins, peptides, polysaccharides, lipids and oligonucleotides (Kellar and Ianonne, 2002;Dunbar et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] In this report, we describe the application of newly available fluorescent microbeads, which are also magnetic. The spectrally unique, magnetic beads have a diameter of 6.5 mmand a surface area of 133 μm2 and, similar to the conventional polystyrene beads, 100 different bead sets are available.…”
Section: Introductionmentioning
confidence: 99%
“…The features of these xMAP systems are listed in Table 3. The xMAP technology has been demonstrated as a powerful multiplexing method and has found applications in detection of human cytokines 40 , single nucleotide polymorphisms (SNPs) 41 , allergy testing 42 , infectious disease diagnosis 43 , and biological warfare agent screening 44 . Another similar optically encoded microsphere based multiplexing platform was developed by Becton Dickinson BioSciences, named Cytometric Bead Array system (BD TM CBA).…”
Section: Encoded-microparticle Arraysmentioning
confidence: 99%